Impact of Social Media and Technology in Undergraduate Business Schools of Pokhara University in Kathmandu - Thapa, Saman (Nepalese Journal of Management, 2025)
This study examines the impact of social media and technology in undergraduate business schools of Pokhara University in Kathmandu. Productivity of students is the dependent variable. The selected independent variables are time spend on social media, purpose of using social media, internet availability, study habits and social support. The primary source of data is used to assess the opinions of respondents regarding time spend on social media, purpose of using social media, internet availability, study habits, social support and productivity of students. The study is based on primary data of 122 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of social media and technology in undergraduate business schools of Pokhara University in Kathmandu. The study showed a negative impact of time spent on social media on productivity of students. It indicates that higher the time spent on social media, lower would be the productivity of students. Similarly, the study showed a positive impact of purpose of using social media on productivity of students. It indicates that different purpose of using social media like for research purpose helps students to achieve a good result. Likewise, the study revealed a positive impact of internet availability on productivity of students. It indicates that higher the internet availability, higher would be the productivity of students. Further, the study showed a positive impact of study habit on productivity of students. It indicates that daily study habits of students lead to increase in productivity of the students. In addition, the study showed a positive impact of social support on productivity of students. It indicates that social encouragement to students lead to increase in productivity of students.